Natural flood management, lag time and catchment scale: Results from an empirical nested catchment study. Issue 3 (4th May 2021) - Black, Andrew; Peskett, Leo; MacDonald, Alan; Young, Andy; Spray, Chris; Ball, Tom; Thomas, Huw; Werritty, Alan
Abstract: Natural flood management (NFM) techniques attract much interest in flood risk management science, not least because their effectiveness remains subject to considerable uncertainty, particularly at larger catchment and event scales. This derives from a paucity of empirical studies which can offer either longitudinal or comparison data sets in which changes can be observed. The Eddleston catchment study, with 13 stream gauges operated continuously over 9 years, is based on both longitudinal and comparison data sets. Two years of baseline monitoring have been followed by 7 years of further monitoring after a range of NFM interventions across the 69 km 2 catchment. This study has examined changes in lag as an index of hydrological response which avoids dependence on potentially significant uncertainties in flow data. Headwater catchments up to 26 km 2 showed significant delays in lag of 2.6–7.3 hr in catchments provided with leaky wood structures, on‐line ponds and riparian planting, while larger catchments downstream and those treated with riparian planting alone did not. Two control catchments failed to show any such changes. The findings provide important evidence of the catchment scale at which NFM can be effective and suggest that effects may increase with event magnitude.